2010
DOI: 10.1016/j.elecom.2010.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Simple immobilization of pyrroloquinoline quinone on few-walled carbon nanotubes

Abstract: Pyrroloquinoline quinone (PQQ) was immobilized on glassy-carbon electrodes (GCE) modified with single-walled carbon nanotubes (SWCNT), few-walled carbon nanotubes (FWCNT) and carbon black (Vulcan XC72R). Modified electrodes were prepared by drop-casting. Immobilization was achieved with an extremely simple dipping procedure and without any further modification to the electrodes. Electrochemical performance of the electrodes was studied by cyclic voltammetry and spectroelectrochemistry. FWCNT adsorbed 30 times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“… Quinoline GCE/MWCNT@QLO − 450 ± 5 64 Hyd 40 4. Pyrroloquinoline quinone GCE/fWCNT +210 Hyd 41 5. Hematin GCE/GMC/Hemt@Chit − 390 − 32 DO, H 2 O 2 42 6.…”
Section: Introductionmentioning
confidence: 99%
“… Quinoline GCE/MWCNT@QLO − 450 ± 5 64 Hyd 40 4. Pyrroloquinoline quinone GCE/fWCNT +210 Hyd 41 5. Hematin GCE/GMC/Hemt@Chit − 390 − 32 DO, H 2 O 2 42 6.…”
Section: Introductionmentioning
confidence: 99%
“…7 Improper orientation of PQQ could affect its reversible oxidation process. Kanninen et al 8 reported the physical adsorption of PQQ to single-walled and few-walled carbon nanotube (FWCNT)-modified glassy carbon electrodes. Multi-walled carbon nanotubes (MWCNTs) are commerically available in different lengths and with different functionalities, which makes them useful for electrode surface modification for improved electrochemical response and for biomolecule immobilization.…”
Section: H3098mentioning
confidence: 99%
“…6,7 These studies can be challenging due to the pH dependence of the redox potentials. 6,8,9 Using a cystamine-monolayer Au-modified electrode, Katz et al6 studied the electrochemistry of PQQ in solution using CV and reported the change in potential with pH to be about 60 mV pH −1 at pH < 6.2; 30 mV pH −1 at 6.2 < pH < 8.6; and about 60 mV pH −1 at pH > 8.6. In another study using PQQ immobilized on few-walled carbon nanotube (FWCNT)-modified glassy carbon electrodes, the change in PQQ's redox potential was estimated to be approximately 67 mV pH −1 , with the highest reversible reduction-oxidation observed at ∼pH 2.…”
mentioning
confidence: 99%
See 2 more Smart Citations